2019
DOI: 10.1111/hex.12931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating community deliberations about health research priorities

Abstract: Context Engaging underrepresented communities in health research priority setting could make the scientific agenda more equitable and more responsive to their needs. Objective Evaluate democratic deliberations engaging minority and underserved communities in setting health research priorities. Methods Participants from underrepresented communities throughout Michigan (47 groups, n = 519) engaged in structured deliberations about health research priorities in professionally facilitated groups. We evaluated some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Another framework, specifically developed to guide genomics activities, uses four themes for deliberative reflection: fairness, context, heterogeneity, and recognizing tensions and conflict ( 61 ). Congruently, we found that participants' deliberation met these and other previously identified quality frameworks ( 48 , 62 , 63 ). Dissimilarly, the current study focused on aspects of quality specific to public policy such as adoption of a societal perspective or “the common good.” This is the idea that what is best for the individual is not always what is best for the larger community.…”
Section: Discussionsupporting
confidence: 62%
“…Another framework, specifically developed to guide genomics activities, uses four themes for deliberative reflection: fairness, context, heterogeneity, and recognizing tensions and conflict ( 61 ). Congruently, we found that participants' deliberation met these and other previously identified quality frameworks ( 48 , 62 , 63 ). Dissimilarly, the current study focused on aspects of quality specific to public policy such as adoption of a societal perspective or “the common good.” This is the idea that what is best for the individual is not always what is best for the larger community.…”
Section: Discussionsupporting
confidence: 62%
“…Public deliberation models also vary in the number of deliberators and the length of the deliberation. For example, one recent deliberation was conducted over two 2-day periods, while others engage fewer people in a single session [ 30 ]. While it is possible that participants’ perspectives may evolve over time and as they develop comfort with their fellow participants, our analysis found that there was positive engagement and candor in the groups in a short time period, comparable to other models [ 16 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one recent deliberation was conducted over two 2-day periods, while others engage fewer people in a single session [ 30 ]. While it is possible that participants’ perspectives may evolve over time and as they develop comfort with their fellow participants, our analysis found that there was positive engagement and candor in the groups in a short time period, comparable to other models [ 16 , 30 ]. Processes such as facilitator training were valuable, as they contributed to standardization in the conduct of small discussions across both sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Effective citizen engagement and public deliberation have been shown to provide rich and nuanced insights on issues of societal importance 32–36 . Structured and meaningful incorporation of these insights into health policy‐making processes helps to legitimize decisions that impact the populace.…”
Section: Introductionmentioning
confidence: 99%
“…Effective citizen engagement and public deliberation have been shown to provide rich and nuanced insights on issues of societal importance. [32][33][34][35][36] Structured and meaningful incorporation of these insights into health policy-making processes helps to legitimize decisions that impact the populace. In many jurisdictions, including Canada, public engagement has been embraced as a component of HTA deliberations, but implementation is variable and best practices for evidence-informed deliberation are still evolving.…”
Section: Introductionmentioning
confidence: 99%